Pregnancy and epileptic seizures in the emergency department setting: A retrospective analysis - Yeliz Simsek; Ayşenur Gür (PLoS ONE, 2026)
Background This study evaluated the clinical features, management, and outcomes of pregnant women with generalized tonic-clonic seizures presenting to the emergency department (ED). The aim was to demonstrate how patients’ clinical features contribute to patient management and prognosis. Methods In this retrospective study, pregnant women over the age of 18 who presented to the ED with generalized tonic-clonic seizures were included. The patients’ demographic characteristics, clinical findings, treatments administered in the ED, and outcomes were recorded. Descriptive statistics, the chi-square tests or Fisher’s exact tests for categorical variables and the Mann–Whitney U or t-test for continuous variables were used in the statistical analysis. Results The study included 48 patients, most of whom were in their third trimester. Thirty-three (69%) patients had a history of epilepsy, and 28 (58.3%) were using antiseizure medications (ASMs). The most commonly used ASM was levetiracetam. Seven (14.6%) patients had suspected eclampsia, and seizure control was achieved in four of them by administering ASMs in addition to magnesium sulfate treatment. Two (4.2%) patients developed status epilepticus (SE). A significant relationship was observed between gestational age and hospitalization (p = 0.005). Conclusion The diagnostic complexity of epileptic seizures in pregnancy complicates treatment choices, and ASM use may also be beneficial in managing eclampsia.